Rheumatoid arthritis-associated autoantibodies and subclinical interstitial lung disease: the Multi-Ethnic Study of Atherosclerosis. Issue 12 (8th September 2016) - Bernstein, Elana J; Barr, R Graham; Austin, John H M; Kawut, Steven M; Raghu, Ganesh; Sell, Jessica L; Hoffman, Eric A; Newell, John D; Watts, Jubal R; Nath, P Hrudaya; Sonavane, Sushil K; Bathon, Joan M; et al.
Abstract : Background: Adults with interstitial lung disease (ILD) often have serologic evidence of autoimmunity of uncertain significance without overt autoimmune disease. We examined associations of rheumatoid arthritis (RA)-associated antibodies with subclinical ILD in community-dwelling adults. Methods: We measured serum rheumatoid factor (RF) and anticyclic citrullinated peptide antibody (anti-CCP) and high attenuation areas (HAAs; CT attenuation values between −600 and −250 Hounsfield units) on cardiac CT in 6736 community-dwelling US adults enrolled in the Multi-Ethnic Study of Atherosclerosis. We measured interstitial lung abnormalities (ILAs) in 2907 full-lung CTs at 9.5-year median follow-up. We used generalised linear and additive models to examine associations between autoantibodies and both HAA and ILA, and tested for effect modification by smoking. Results: In adjusted models, HAA increased by 0.49% (95% CI 0.11% to 0.86%) per doubling of RF IgM and by 0.95% (95% CI 0.50% to 1.40%) per RF IgA doubling. ILA prevalence increased by 11% (95% CI 3% to 20%) per RF IgA doubling. Smoking modified the associations of both RF IgM and anti-CCP with both HAA and ILA (interaction p values varied from 0.01 to 0.09). Among ever smokers, HAA increased by 0.81% (95% CI 0.33% to 1.30%) and ILA prevalence increased by 14% (95% CI 5% to 24%, ) per RF IgM doubling; and HAA increased by 1.31% (95% CI 0.45% to 2.18%) and ILA prevalence increased by 13% (95% CI 2% to 24%) per anti-CCP doubling. Among never smokers, no meaningful associations were detected. Conclusions: RA-related autoimmunity is associated with both quantitative and qualitative subclinical ILD phenotypes on CT, particularly among ever smokers.